Students' Perception Analysis of the Effectiveness of the Beelinguapp Application as a Learning Medium in Improving Listening Skills - Alia Riska Sipayung, Sefia; Safithri Armin, Diah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze students' perceptions of the effectiveness of the Beelinguapp application as a learning medium to improve listening skills. The research was conducted on students of the English Education Study Program at the State Islamic University of North Sumatra in 2024, involving 50 respondents. The study used a convergent mixed-method design, which integrates quantitative and qualitative approaches. The research instruments consisted of a 15-item Likert scale questionnaire measuring perceptions of ease of use, perceptions of improvement in listening skills, and learning motivation, as well as five open-ended questions to explore students' experiences and views. Quantitative data were analyzed descriptively using percentages and frequencies, while qualitative data were analyzed through thematic analysis. The research results show that the majority of students perceive Beelinguapp as easy to use, effective in improving listening skills, and capable of enhancing learning motivation. The bilingual text feature integrated with audio is considered helpful for students to understand pronunciation, intonation, and vocabulary in context. Nevertheless, some technical issues, such as audio speed and limited internet access, are still experienced by some respondents. Overall, Beelinguapp has the potential to become an effective supporting medium for listening learning, particularly in mobile-based self-directed learning.